Polacy wobec transformacji systemowej. Refleksje po wyborach parlamentarnych 19 września 1993 r. - Ziółkowski, Marek; Drozdowski, Rafał (Wydział Prawa i Administracji UAM, 1993)
The results of the parliamentary elections of September 1993 mark the end of a certain phase of the system transformation process started in 1989. These results are analysed at two different levels: (1) t h e distribution of the popular voltes which reflects a growing societal apprehension of the social consequences of t he transformation, which resulted in a visible but not dramatic shift of the political attitudes to the left; (2) the final outcome of the elections i.e. the distribution of parliamentary seats which reflects not so much the electoral behaviour of the society as the electoral mistakes of the political elites of the post-Solidarity parties.
Poles towards the system transformation. Sociological reflections after the parlament ary elections of 19 September 1993